Severe Malaria in an Adult Patient from Low-Endemic Area in Flores Island, East Nusa Tenggara - Maria Teressa; Asep Purnama; Joshua Henrina; Agustinus Wiraatmadja; Angela M. B. Boro; Candida I. L. Sam; Tersila A. D. Dedang; Alius Cahyadi (Case Reports in Medicine)
Malaria is an infection caused by protozoa of the genus Plasmodium, commonly found in tropical and subtropical regions worldwide. Plasmodium falciparum causes the most severe form of the disease and may progress to life-threatening manifestations. This case describes a 26-year-old man who suffered cerebral malaria with multiple organ dysfunction and successfully recovered despite poor initial prognosis. Negligent and late diagnosis of malaria leads to severe complications and a worse prognosis. This case emphasizes despite living in a low-endemic malaria area, physicians should remain meticulous and consider malaria as differential diagnosis even after initially presenting with nonspecific symptoms. Consequently, malarial screening should be performed to modify the risk of mortality. Furthermore, close monitoring and early administration of intravenous artesunate are also particularly critical.